Effect of aerobic and resistance exercises on body composition and quality of life in overweight and obese women: a randomized control trial (Universa Medicina, 2023)
BackgroundObesity has become a major health issue in the world and directly reduces the quality of life. The aim of this study was to compare the effect of aerobic and resistance exercises on body composition and quality of life (QoL) in overweight and obese women.Method An experimental study involving 90 overweight/obese women aged between 20-45 years participated in the study voluntarily and were randomized into control (n=30), aerobic exercise (AE) (n=30), and resistance exercise (RE) (n=30) groups. Either AE or RE groups performed exercise for 60 minutes per day for 10 weeks, whereas the control group did not perform any exercise. The body composition and QoL of the women were measured before and after the exercise.ResultsBody weight, BMI, fat mass, and waist and hip circumferences decreased significantly in both AE and RE groups after the exercise intervention compared to the control group (p